Beberapa Faktor yang Berhubungan dengan Kejadian HIV/AIDS pada Wanita (Studi Kasus di Kabupaten Kendal) - Siti Musyarofah; Suharyo Hadisaputro; Budi Laksono; Muchlis Achsan Udji Sofro; Lintang Dian Saraswati (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2017)
Background: HIV/AIDS are major problem that threatens Indonesia and many countries around the world. In 2011 there were 17.3 million adults living with AIDS were women. The purpose of studies proved that host and environmental factors were associated the occurence of HIV/AIDS in women. Method: The research using case-control study, was supported by indepth interview. The target population were women in Kendal with a sample of 76 women consisted of 38 women with HIV/AIDS and 38 women negative HIV. Samples case with consecutive sampling technique, control with cluster sampling. Bivariate analysis using chi-square test and multivariate analysis used logistic regression. Results: Multivariate analysis showed that host factors signiﬁcantly associated with the occurence of HIV/AIDS in women were the number of sexual partners more than 1 (p = 0,003), level of education was low ≤ 9 years (p = 0,049) and the ﬁrst married age < 20 years (p = 0,03); environment factors signiﬁcantly associated was history of HIV/AIDS on her husband (p=0,001). Host factors were not signiﬁcantly associated with the occurence of HIV/AIDS in women were history of receiving blood donors, history of sexually transmitted diseases, the status of drug users, the habit of drinking alcohol, violence, type of job, and socioeconomic. Conclusion: Host factors signiﬁcantly associated with the occurence of HIV/AIDS in women were the number of sexual partners more than 1, level of education was low ≤ 9 years, and the ﬁrst married age <20 years; environment factors signiﬁcantly associated was history of HIV/AIDS on her husband. Background:HIV/AIDSaremajorproblemthatthreatensIndonesiaandmanycountriesaround theworld.In2011therewere17.3millionadultslivingwithAIDSwerewomen.Thepurposeof studiesprovedthathostandenvironmentalfactorswereassociatedtheoccurenceofHIV/AIDS inwomen.Method:Theresearchusingcase-controlstudy,wassupportedbyindepthinterview.Thetarget population were women in Kendal with a sample of 76 women consisted of 38 women with HIV/AIDSand 38 women negative HIV. Samples case with consecutive sampling technique, controlwithclustersampling.Bivariateanalysisusingchi-squaretestandmultivariateanalysis usedlogisticregression.Results: Multivariateanalysisshowedthathostfactorssigniﬁcantlyassociatedwiththe occurenceofHIV/AIDSinwomenwerethenumberofsexualpartnersmorethan1(p=0,003), levelofeducationwaslow≤9years(p=0,049)andtheﬁrstmarriedage<20years(p=0,03); environmentfactorssigniﬁcantlyassociatedwashistoryofHIV/AIDSonherhusband(p=0,001).HostfactorswerenotsigniﬁcantlyassociatedwiththeoccurenceofHIV/AIDSinwomen were history of receiving blood donors, history of sexually transmitted diseases, the status of drugusers,thehabitofdrinkingalcohol,violence,typeofjob,andsocioeconomic.Conclusion: Host factors signiﬁcantly associated with the occurence of HIV/AIDS in women werethenumberofsexualpartnersmorethan1,levelofeducationwaslow≤9years,andtheﬁrst marriedage<20years;environmentfactorssigniﬁcantlyassociatedwashistoryofHIV/AIDSon herhusband.